2010
DOI: 10.12681/mms.88
|View full text |Cite
|
Sign up to set email alerts
|

The response of benthic foraminifer, ostracod and mollusc assemblages to environmental conditions: a case study from the Camalti Saltpan (Izmir-Western Turkey)

Abstract: The subject of this report is benthic foraminifer populations preserved in the saltpan of Camalti in the Province of Izmir. High salinity in certain habitats of Ammonia tepida Cushman may be the primary cause of the high rate of twins and triplets as well as other morphological abnormalities recorded within this species (50 % as compared to an anomaly rate of 1 % in normal marine waters). Thicker cyst membrane developing in extremely saline environments may encourage twins and other morphological deformities b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
9
0
3
Order By: Relevance
“…This species is commonly found in environments with high concentrations of organic matter (Loureiro et al, 2009) and was observed in most stations, but had higher density values in the stations GD04 and GD05, located in a tributary channel. In these stations, a large number of ostracods juveniles were observed, possibly because they are more sheltered areas that favor the reproduction of this mesohalin species (Meric et al, 2010).…”
Section: Ecological Parametersmentioning
confidence: 99%
“…This species is commonly found in environments with high concentrations of organic matter (Loureiro et al, 2009) and was observed in most stations, but had higher density values in the stations GD04 and GD05, located in a tributary channel. In these stations, a large number of ostracods juveniles were observed, possibly because they are more sheltered areas that favor the reproduction of this mesohalin species (Meric et al, 2010).…”
Section: Ecological Parametersmentioning
confidence: 99%
“…obs. unpublished data), Bursa (Altınsaçlı and Griffiths 2001a); Balıkesir (Altınsaçlı and Griffiths 2001b); Düzce (Gülen 1985); Afyon (Gülen 1985); Denizli (Altınsaçlı and Mezquita 2008); İzmir (Meriç et al 2010); Isparta (Özuluğ et al 2001); Konya (Akdemir 2004); Aksaray (Altınsaçlı 2004); Şanlıurfa (Özuluğ and Dökümcü 2014); Diyarbakır (Gülen et al 1996;Akdemir and Külköylüoğlu 2011); Erzincan (Akdemir and Külköylüoğlu 2014).…”
Section: Study Sites and Samplingunclassified
“…Druh Diodora italica je v recentu vázán převážně na hloubky od 10-60 m (Russo 2017). V podobné hloubce žije také druh Pseudochama gryphina (Meric et al 2010). Převážně v mělkých vodách jsou rozšířeni zástupci čeledi Conidae, kteří jsou na lokalitě zastoupeni větším množstvím druhů (Chira, Voia 2001;Harzhauser, Landau 2016).…”
Section: Paleoekologieunclassified